Reflexividade e agência na teoria sociológica contemporânea - Camila Penna (Ciências Sociais Unisinos, 2012)
The article discusses some of the contributions of contemporary sociological theory to the debate on agency and on reflexivity and traces the position of relevant authors in the current theoretical production regarding the work of the sociologist and the role of sociology. The discussion is developed through the idea of spectrum, along which different theories are positioned according to the capacity of agency and of reflexivity ascribed to the actors. "Capacity of agency and reflexivity" refers to the level of consciousness, reflection, autonomy and the capacity of producing effects ascribed to the actor. The spectrum would be configured, using Garfinkel's (1967) concepts as analytical tools, at one of the poles by the concept of "cultural dope" and at the other by the notion of "lay sociologist". Along the spectrum are located different orientations on contemporary sociological theory. We argue that the position each author takes in relation to the capacity of agency and reflexivity is related to his or her perception of the role of sociology and of the sociologists' work.